INTERAKSI SOSIAL ANTARA WARGA PERMUKIMAN REAL ESTAT DENGAN PENDUDUK DI SEKITAR NYA - Rahardjo, Parino; Nuzzela, Softy (Universitas Tarumanagara, 2021)
The Bonana settlement is located in Cilandak sub-district, Lebak Bulus village. Built on an area of 38 hectares, it is the result of the conversion of gardens and swamps owned by residents who currently still live in the villages around the settlement. In general, those who work in the Bonana Settlement, live in the villages around the Bonana settlement. The Bonana settlement is equipped with public and social facilities. The Bonana settlement is equipped with green open spaces, in the form of gardens, tennis courts, and green open spaces along the main drainage channel. Green open space equipped with a children's play area (playground), basketball and badminton courts and mosque worship facilities. The facilities in the Bonana Settlement are also used by residents around the Bonana Settlement. Within the Settlement, the formal economic facilities built by the developer are shops with banking facilities, household needs, medical needs, and places to eat, in addition there is an informal market that sells daily necessities. This informal market was formed by the trading community. In general, settlements built by developers are generally closed to the surrounding community, as a preventive measure against crime, but the Bonana Settlement is open between residents of the settlement and the surrounding community. The purpose of the study was to determine the form of participation of the residents of the Bonana Settlement to maintain the security and comfort of their settlements. The study used a qualitative approach with data collection by interviews and observations, and by using sources. The study obtained the participation of residents of the Bonana Settlement to make a safe and comfortable settlement. Keywords: Community; Social Interaction; Green Open Space; Public Open Space AbstrakPermukiman Bonana, berlokasi di Kecamatan Cilandak, kelurahan Lebak Bulus. Dibangun pada lahan seluas 38 Ha, merupakan hasil konversi kebun dan rawa milik penduduk yang saat ini sebagian masih mendiami perkampungan di sekitar Permukiman tersebut. Pada umumnya mereka yang bekerja di Permukiman Bonana, bertempat tinggal di perkampungan disekitar permukiman Bonana. Permukiman Bonana dilengkapi dengan fasilitas umum dan sosial. Permukiman Bonana di lengkapi dengan Ruang Terbuka Hijau, berupa taman, lapangan tenis, dan ruang terbuka hijau sepanjang saluran utama drainase. Ruang terbuka hijau yang dilengkapi dengan tempat permainan anak (playground), lapangan basket dan bulu tangkis dan fasilitas peribadatan masjid. Sarana yang ada di dalam Permukiman Bonana dimanfaatkan juga oleh warga sekitar Permukiman Bonana. Di dalam Permukiman, fasilitas ekonomi formal yang dibangun oleh pengembang berupa pertokoan dengan fasilitas perbankan, kebutuhan rumah tangga, kebutuhan medis, dan tempat makan, di samping itu terdapa terdapat pasar informal yang menjual kebutuhan sehari-hari. Pasar informal ini dibentuk oleh masyarakat pedagang. Pada umumnya permukiman yang dibangun oleh pengembang umumnya tertutup terhadap masyrakat sekitarnya, sebagai tidakan preventif terhadap tindak kriminal, namun Permukiman Bonana terbuka antara warga permukiman dengan masyarakat sekitar. Tujuan penelitian mengetahui bentuk partisipasi warga Permukiman Bonana untuk menjaga keamanan dan kenyamanan permukimannya. Penelitian menggunakan pendekatan kualitatif dengan pengumpulan data dengan wawancara dan observasi, dan dengan menggunakan narasumber. Penelitian mendapatkan partisipasi warga Permukiman Bonana untuk menjadikan permukiman yang aman dan nyaman.